Upaya Penurunan Nyeri Akut Pada Pasien Congestive Heart Failure - Anggriana, Gustia; , Ns.Arief Wahyudi J, S.Kep.M.kep (2017)
Background: The incidence of heart failure in Indonesia has increased from year to year.. Furthermore, heart failure cause the appearance of symptoms such as chest pain. Chest pain appear because the supply of oxygen to the myocardium decreases, and will impact the death of heart cells. If pain is left alone, the severity of the pain to be increased. Finally, will lead to neurological shock to the this person.. Objective: Describing the efforts to reduce acute pain in patients with heart failure. Methods: The method used a descriptive method with case study approach, in Hospital on February 11 to 13, 2017. The data was collected through observation, physical examination, medical records, interviews, documentary studies of journals and books and journals supported. Results: Patients showed a decrease of chest pain after the action. There is an effect of relaxation action deep breath, warm compresses and progressive relaxation to reduce chest pain. Conclusion: The act of relaxation breaths, warm compresses and progressive relaxation effectively lower chest pain. Suggestion: Actions relaxation deep breath, warm compresses and progressive relaxation can be as inputs in independent nursing action to deal with the pain. Keywords: pain, heart failure, relaxing breaths, warm compresses, progressive relaxation.